The simultaneous extraction and depolymerisation of lignin, from vine shoots using one-pot microwave-assisted deep eutectic solvent systems - Scholtz, Nicholas Edward (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.